2010
DOI: 10.1038/sj.bjc.6605635
|View full text |Cite
|
Sign up to set email alerts
|

Clinical responses observed with imatinib or sorafenib in melanoma patients expressing mutations in KIT

Abstract: BACKGROUND: Mutations in KIT are more frequent in specific melanoma subtypes, and response to KIT inhibition is likely to depend on the identified mutation. METHODS: A total of 32 patients with metastatic acral or mucosal melanoma were screened for mutations in KIT exons 11, 13 and 17. RESULTS: KIT mutations were found in 38% of mucosal and in 6% of acral melanomas. Three patients were treated with imatinib and one with sorafenib. All four patients responded to treatment, but three have since progressed within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 23 publications
1
54
1
1
Order By: Relevance
“…The finding of KIT mutations in mucosal melanoma has opened the door for targeted therapy as a treatment option for this subtype of melanoma. Indeed, an increasing number of case studies have shown clinical responses of KIT-mutated mucosal melanomas to tyrosine kinase inhibitors such as imatinib (13)(14)(15)(16), sorafenib (16,17), and dasatinib (18). Preliminary data from an ongoing phase II study also show promising results, with varying degrees of response to imatinib in KIT-mutated melanomas (19).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The finding of KIT mutations in mucosal melanoma has opened the door for targeted therapy as a treatment option for this subtype of melanoma. Indeed, an increasing number of case studies have shown clinical responses of KIT-mutated mucosal melanomas to tyrosine kinase inhibitors such as imatinib (13)(14)(15)(16), sorafenib (16,17), and dasatinib (18). Preliminary data from an ongoing phase II study also show promising results, with varying degrees of response to imatinib in KIT-mutated melanomas (19).…”
Section: Introductionmentioning
confidence: 75%
“…However, cells with the L576P mutation seem to be relatively resistant to imatinib, but are sensitive to dasatinib (18). Clinically, mucosal melanoma patients with KIT mutations located outside position L576 have been responsive to imatinib (13,14,16) and sorafenib (16,17), whereas patients with L576P mutant tumors responded to dasatinib (18). More recently, those with L576P mutated mucosal melanomas were also described as responsive to imatinib (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, KIT-activating (v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog) mutations are reported to be associated with a variety of malignant neoplasms and specific chemotherapeutic agents (imatinib and sorafenib) are available. 12,13 Clinical experience in patients with gastrointestinal stromal tumor indicates that the presence and location of specific KIT mutations can predict sensitivity and resistance patterns to KIT kinase inhibitors. 14 To investigate whether metastasizing adnexal carcinomas possess activation of oncogenic pathways that can be targeted by available chemotherapeutic agent, we performed immunohistochemistry for EGFR, HER2, and CD117 (KIT) expression; fluorescence in situ hybridization (FISH) for EGFR and ERBB2 gene amplification; and molecular analyses for recurrent mutations in 15 cancer genes including BRAF, EGFR, KRAS, PIK3CA, and TP53 on cases of adnexal carcinomas with metastases.…”
mentioning
confidence: 99%
“…As a rule, c-Kit expression is lost during melanoma progression, but a subset of melanomas has been found to overexpress it and mutations activating c-Kit, mostly constituted by L576P (up to 50% of mutations), have recently been identified in some mucosal and AL melanoma subtypes (5-20% of cases), but not in cases arising from chronic sun-damaged skin (Rother & Jones, 2009;Monsel et al, 2010). KIT is expressed at maximum level at the invading edge of tumors, this suggesting a role for dynamic RTK activation in metastasis (Handolias et al, 2010). Monsel et al (Monsel et al, 2010) demonstrated that c-Kit mutated melanocytes require a specific epigenetic environment to be transformed in melanoma cells.…”
Section: Ckitmentioning
confidence: 99%